Case Report: Prolonged DAWS in an RLS patient under severe relational stress - Gillon, Michaël (Frontiers in Human Neuroscience, 2026)
BackgroundDopamine agonist withdrawal syndrome (DAWS) is a severe condition reported primarily in Parkinson's disease (PD) but increasingly recognized in restless legs syndrome (RLS). While DAWS is classically associated with high-dose dopamine agonists (DAs) in Parkinson's disease, it has also been reported in RLS patients treated with low-dose therapy (≤ 0.75 mg pramipexole equivalent), although such cases remain rare. While direct evidence is lacking, psychological and relational stressors, in conjunction with prior medication adjustments, could plausibly modulate DAWS severity through a mechanism akin to kindling.Case presentationWe describe the case of a 51-year-old male who developed severe DAWS after withdrawing from low-dose pramipexole (0.26 mg) prescribed for RLS. A 6-month venlafaxine taper, completed 2 weeks before DA tapering, may have increased neurochemical vulnerability. Initial dose reduction caused akathisia, tremors, panic attacks, RLS worsening, and depressive symptoms. After brief reinstatement, abrupt cessation triggered painful electric-like sensations in the lower back and emotional collapse. The patient was transitioned to rotigotine (2 mg/day), together with other psychotropic medications, which provided partial and temporary relief. Symptoms relapsed during tapering, with marked worsening occurring in parallel with episodes of severe relational stress within a close personal connection. Clinical assessments explored these interactions as potential psychological stressors, as reported by the patient. Given the temporal association between these stressors and symptom relapses, relational factors may have contributed to the severity and recurrence of DAWS episodes. At 13 months after complete DA discontinuation, the patient has regained nearly full functionality, although episodes of marked fatigue and significant bedtime RLS persists.Discussion and conclusionThis case illustrates that DAWS can occur in RLS patients even at low DA doses, with atypical symptoms possibly involving autonomic and central sensitization. Relational stress may significantly exacerbate symptom severity, potentially leading to profound neurological destabilization through mechanisms such as cross-system hypersensitivity or a kindling-like process, as suggested by existing literature. This factor may need to be systematically assessed in DAWS management. As a rare patient-authored account, this report contributes to the understanding of DAWS in non-PD populations and highlights the need for longitudinal research to guide safer withdrawal protocols and integrated care.